Family factors associated with dental caries among 5-year-old preschool children - Castilho, Giovanna Torqueto [UNESP]; Pessoa, Marília Narducci [UNESP]; de Oliveira, Caroline Correa [UNESP]; de Melo, Letícia Santos Alves [UNESP]; Tagliaferro, Elaine Pereira Silva [UNESP]; Pardi, Vanessa (Frontiers, 2024)
Background: Although dental caries is largely preventable, it remains highly prevalent among children. Aim: Evaluate family factors associated with the prevalence of dental caries in 5-year-old children. Design: This cross-sectional study recruited 5-year-old children from public preschools in Araraquara, São Paulo, Brazil. Data on sociodemographic factors, family routines, and oral health practices were gathered via a self-administered questionnaire completed independently by caregivers. Children received a dental clinical examination at school and caries experience was recorded using the dmft and SiC (Significant Caries index) indexes following the World Health Organization (WHO) criteria. Results: Data analysis was performed using Chi-square and multiple logistic regression using a significance level of 5%. Of the 578 children in the study, 67.3% were caries-free. The mean dmft index was 1.14 (SD = 2.24), while the SiC index stood at 3.46 (2.69). Factors such as income, caregiver assistance with toothbrushing, caregiver perception of child and parent oral health, and prioritization of dental visits within the family were associated with caries presence. Conclusions: Overall, dental caries prevalence was low in this population, with family factors demonstrating significant associations with dental caries. The attitudes of caregivers regarding oral health appear to wield considerable influence over the dental health of their children.
Keywords: dental caries; family; oral health; oral health perception; toothbrushing